Oxidised biochar from palm kernel shell for eco-friendly pollution management / Sylbialin Amin, Robert Thomas Bachmann and Soon Kong Yong - Amin, Sylbialin; Bachmann, Robert Thomas; Yong, Soon Kong (Universiti Teknologi MARA Shah Alam, 2020)
Oil palm plantations produce palm kernel shell (PKS) that can be converted into biochar for environment-friendly soil remediation and water treatment. Oxidation with hydrogen peroxide (H2O2) may enhance surface characteristics and the quality of low-rank PKS biochar as a sorbent for environmental decontamination. This study aims to determine the effect of oxidation on the surface characteristics (i.e., specific surface area, surface charge, and chemical properties) of PKS biochar, and compared with that of PKS activated carbon. The surface area for the oxidised PKS biochar was similar to that of PKS biochar, indicating that oxidation did not remove the pore blocking material from the surface area of the PKS biochar. However, oxidation has increased the amount of negatively charged oxygen functional groups in PKS biochar, as indicated by the analyses of the Fourier transform infrared spectroscopy (FTIR) and cation exchange capacity (CEC). The CEC value of raw and activated PKS biochar were similar and 4.6 and 2.6 times lower for PKS biochar and oxidised PKS biochar, respectively. Oxidation caused enlargement of pores on PKS biochar and caused a reduction of specific surface area. More research is required to establish the process conditions to create a greater surface area and sorption capacity